Angiotensin II in arterial and renal venous plasma and renal lymph in the dog - Bailie, Michael D. (1971)
Angiotensin II was determined by radioimmunoassay in systemic arterial, pulmonary arterial, and renal venous plasma and in renal hilar lymph in dogs. Levels of the peptide were determined prior to and during progressive graded hemorrhage or reduction in renal perfusion pressure. Levels of angiotensin II in plasma consistently rose during transit through the lung indicating pulmonary conversion of angiotensin I to angiotensin II. On the other hand, angiotensin II in the renal vein plasma was less than that in arterial plasma indicating renal extraction of the peptide from plasma. When renal hilar lymph was sampled under similar conditions, angiotensin II in lymph was consistently higher than that in arterial or renal venous plasma. Furthermore, in some experiments angiotensin II in lymph increased at a time when the concentration in plasma was undetectable. No evidence was found to indicate that angiotensin II in plasma entered renal lymph. It was concluded that angiotensin II levels in lymph reflected the concentration of angiotensin II in renal tissue. The data further suggested that angiotensin II is partially removed from arterial plasma by hydrolysis during transit through the kidney.